The Influence Of Perceived Social Media Marketing Elements On Consumer Brand Engagement And Brand Awareness Of The Pijak Bumi Brand On Instagram - Tegar Prasetyo; Erlita Ridanasti (Cita konsultindo, 2024)
Social media has become an important tool in modern marketing strategies, allowing companies to reach a wider demographic in a more effective and measurable way. The purpose of this study is to examine the effect of perceived social media marketing elements on consumer brand engagement so as to increase brand awareness. The research method uses a quantitative approach by distributing questionnaires to 180 respondents who know Pijak Bumi's environmentally friendly products. Data analysis was conducted using PLS-SEM with SmartPLS 3.29 software. The results stated that social media marketing elements including entertainment, interaction, trendiness, and EWOM have a positive and significant effect on consumer brand engagement. The results also state that consumer brand engagement has a positive and significant effect on brand awareness.